Structural domains of Porphyromonas gingivalis recombinant fimbrillin that mediate binding to salivary proline-rich protein and statherin. - Amano, A (1996)
Fimbriae (the oligomeric form of fimbrillin) are considered important in the adherence and colonization of Porphyromonas gingivalis in the oral cavity. In the present study, we have identified the structural domains of P. gingivalis fimbrillin that mediate the binding to salivary proline-rich protein 1 (PRP1) and statherin. A series of synthetic fimbrillin peptides were used to localize the active fimbrillin domains involved in the binding to PRP1 and statherin. The binding of 125I-labeled 41-r-Fim (whole-length recombinant fimbrillin, amino acid [aa] residues 1 to 337) to PRP1-coated hydroxyapatite beads (HAP) was strongly inhibited by the fimbrillin C-terminal peptides corresponding to aa residues 266 to 286 and 318 to 337 (peptides 266-286, and 318-337, respectively), while the binding to statherin was inhibited by C-terminal peptides 266-286, 293-306 and 307-326. Peptide 126-146 also showed a weak inhibitory effect, about half that of other active peptides, on the binding to both PRP1 and statherin. P. gingivalis whole-cell binding to PRP1- or statherin-coated HAP was inhibited by more than 80% by the same active peptides. To confirm that the C-terminal portion of fimbrillin includes domains responsible for the binding, two C-terminally truncated variants of recombinant fimbrillin were generated and purified. These were designated 34.5-r-Fim, corresponding to aa residues 1 to 286, and 32-r-Fim, corresponding to aa residues 1 to 265. 125I-34.5-r-Fim revealed 35 and 34% loss of binding ability to PRP1 and statherin, respectively. 125I-32-r-Fim had significantly less binding ability to PRP1 and statherin than 125I-34.5-r-Fim, which was reduced 78 and 73%, respectively. Whole-cell binding to PRP1-, statherin-, or whole saliva-coated HAP was inhibited up to 100% by 41-r-Fim, while 32-r-Fim also showed considerable inhibition, possibly due to the region of aa 126 to 146. Collectively, these results suggest that there are separate and multiple binding sites for PRP1 and statherin in the P. gingivalis fimbrillin, and the combination of all of these binding sites may be indispensable in establishing stable bacterial adherence to saliva-coated surfaces in the oral cavity.